Influence of cognitive neural mechanism on music appreciation and learning - Lv Yang (De Gruyter, 2019)
Based on the related research results of the relationship between cognitive neural mechanism and music in recent years. In this paper, we study the relationship between the cognitive neurons and music from the overlapping and separation of brain neuro-mechanism and the significance of functional relationships between the two. Through analysis, it can be seen that the cognitive neural mechanism has a certain influence on music appreciation and learning and the studies on brain-damaged patients show that the two may have separate and independent neural bases. Finally, we find the influence of sub-consciousness on decision making through the measurement of SCRs (skin conductance responses), and thus propose a decision model modified by subconscious and make an outlook for future research trends.